Psychological Evaluation in Rosacea Patients: A Case- Control Study using Symptom Checklist -90 - Revised - Tavares-Bello, Rui (2016)
Background: Rosacea, a prevalent chronic facial skin condition, is classically referred to as a “psychodermatosis”, in that psychological factors are relevant both in its initiation and course. Rosacea patients have been described as immature, anxious, with diminished self-esteem and with feelings of guilt and shame, or as psychoneurotic, with hysterical or obsessive compulsive configurations.Objective: In this study we investigated the psychopathological distress experienced by rosacea patients, as compared to a group of dermatological patients suffering from acute, non-conspicuous, accidental dermatoses. One additional purpose was to assess the influence that demographic features and clinical factors had on final results.Patients/Methods: A total of 243 patients with rosacea, aged from 18 to 72 years’ old were enrolled from an outpatient dermatology clinic in a hospital setting. Rosacea was objectively rated and disease duration recorded. The SCL-90 (R) was used to assess participants psychological distress and to record emotional and psycho vegetative complaints.Results: Statistical analysis revealed a definite independent influence of the variables rosacea, gender, school level, and also of the interaction rosacea/gender on the psychometrical variables. Rosacea patients scored higher than controls with respect to interpersonal sensitivity (F[1,241]=3.57, p<0.01). Concerning gender differences, female patients scored always higher than controls in anxiety, depression, interpersonal sensitivity, obsession-compulsion, paranoid ideation and somatization, whereas male patients did so only for interpersonal sensitivity. As to the effects of disease duration, rosacea patients’ for more than one year revealed significantly higher scores of paranoid ideation than patients’ with less than one year duration (F[2,52]=3.79, p<0.05).Conclusions: Patients suffering from rosacea – as opposed to other dermatoses – do experience significant psychosocial distress, which was nevertheless found to be unrelated to disease clinical sub-type.